Effects of Geometric Confinement on Zero-Gravity Droplets between Two Parallel Planes - Lv, Cunjing (Langmuir : the ACS journal of surfaces and colloids, 2020)
Investigation of geometric effects on confined droplets is important for the fundamental understanding of the ubiquitous wetting phenomena in nature as well as for a variety of practical applications. In this study, the effect of geometric confinement on the wetting behavior of a droplet confined between two parallel rigid planes was investigated. The closed solutions of the Young-Laplace equation were derived through an analytical method. These solutions are applicable for arbitrary values of the contact angles and the ratio of the size of the droplet to the separation of the planes. For completely nonwetting and wetting cases, an asymptotic method was employed, and the sophisticated analytical solutions of the Laplace pressure, droplet volume, surface energy, and capillary force were expressed as functions of the size and the separation of the droplet in a simple way. In order to check the applicability of the results, experiments were designed to counteract the gravity of the droplets. The asymptotic results not only quantitatively agree well with the theoretical and experimental results over a large range of the parameter space, but also provide a straightforward view for reflecting the effect of the geometric confinement on the wetting behaviors of droplets